Parenting in the Z-Generation Era - Wahyuni, Henny Fitri; Carolina, Carolina; Puspita, Yenny; Effendi, Darwin (PPSDP International Journal of Education, 2023)
Parenting or the upbringing of teachers and parents towards children is a fundamental and important thing in human life especially in facing the challenges of the times. Along with the development of the times, human technology is also developing. However technological developments do not only have positive impacts on human life, particularly on youths but also have negative impacts, in this case, the misuse of internet technology. Looking at the many cases of bullying, violence against children, teenage brawls, and cases that show moral degradation in today’s youths certainly make everyone sad, especially parents and teachers. So, this article was written with the aim of describing parenting in an era where internet development was very rapid or an era called the Z generation or internet generation which is expected to be useful for parents and teachers to guide the nation’s next generation in an era of technological or internet development. In this study, the writers used a literature review that was sourced from the results of research that had been carried out, books, which were listed online and in print. The result of this literature study shows the many methods or patterns of parenting currently being developed by parenting experts. But as parents and teachers, of course, we have to choose the most appropriate parenting pattern in accordance with the demands of the times.